The development of knowledge on natural history and collection of naturals in the European medieval culture - O. V. Chervonenko (History of science and technology, 2017)
The present paper deals with the history of development of knowledge on natural history as well as of collections of natural objects. Church treasures are considered here as primary stages of formation of museum collections. Sacral facilities, their design including highly artistic works, and the emotial impact they caused on people allow considering them as prothotypes of museum exhibitions.